RESULTS OF BIODEGRADABLE VASCULAR ENDOPROSTHESES IMPLANTATION IN ISCHEMIC HEART DISEASE PATIENTS WITH TYPE 2 DIABETES - Z. Kh. Shugushev; D. A. Maksimkin; Yu. S. Vorob'eva; A. G. Chepurnoj; G. I. Veretnik; A. G. Fajbushevich (Российский кардиологический журнал)
Aim. To evaluate efficacy of endovascular treatment in patients with diabetes, operated with biodegradable vascular endoprostheses and everolimus eluting stents.Material and methods. Primarily, 143 patients were selected into the study. Then 125 patients included and randomized to 2 groups. Patients of I group (n=57) underwent implantation biodegradable vascular endoprostheses, and the II group (n=68) — coronary stents eluting everolimus. For the control of biodegradable endoprostheses implantation optical coherent tomography was used, that was performed at the end of intervention and in long-term follow-up by 12 months. Results. Totally, 63 biodegradable vascular endoprostheses implanted to the patients of I group, and 102 everolimus coated stents to II group patients. Mean diameter of implanted endoprostheses in group I was — 2,88±0,06 mm, and in group II — 2,68±0,12 mm (р>0,05). Technical success of intervention was 100% in both groups. Total number of serious cardiovascular complications during in-patient phase was 3,5% and 2,94% in groups, respectively (p>0,05). Long-term results were followed-up in 41 patient from group I and in 52 from group II. In 12 months survival rate was 100%. Prevalence of non-fatal MI among I and II group patients was 4,9% and 3,8%, resp. (p>0,05). The reason was progression of atherosclerotic process in other arteries. Restenosis prevalence that required new intervention on target lesion was 2,4% and 1,9%, resp. (p>0,05). Late thrombosis in long-term follow-up was not marked in both groups. Late loss of intrinsic lumen of the vessel, by the data of optical coherent tomography was 0,14±0,19 mm and 0,12±0,23 mm, respectively, for groups I and II (р>0,05).Conclusion. Biodegradable vascular endoprostheses in CHD patients with diabetes and mostly involvement of middle and distal segments of coronary arteries, showed equal efficacy and safety, with everolimus coated stents, in 12 months after intervention.